Where have all the Ur III seals gone? - Dahl, J (Transnational Press London, 2024)
In this paper I analyse the late 3rd millennium and early 2nd millennium seals in two mid-size collections and reach the conclusion that exceedingly few of them date to the Ur III period (c 2100 – 2000 BC). I include some observations on other collections. I then ask the basic question: where have all the Ur III seals gone? After briefly exploring other options, I suggest with online visual evidence, that the vast majority of the Ur III seals were re-cut in the Old Babylonian period. At the end of the paper, I suggest that the absence or presence of seals from specific periods can be used to model larger historical trends.